Meniti Kualitas Profesionalisme Guru : Transformasi Pendidikan Menuju Masa Depan Yang Berkualitas - Reni Puspita; Linda Asmaraneti; Dwi Noviani; Hilmin Hilmin (Universitas Katolik Widya Karya Malang, 2023)
In the educational context, professional teachers are needed to develop the quality of education for students. Teacher professionalism is the main key to the success of improving the quality of education. Professional teachers are not only required to be able to convey information to students, but are also required to plan, manage, diagnose and assess the process of teaching and learning outcomes. This research aims to examine what professionalism means, what are the characteristics of professional teachers and what are the steps to becoming professional. The approach used in this research is a qualitative approach with a type of library research. Researchers obtain data from books, journals, articles and others related to the theme or title being discussed.